The Influence of Environmental Performance Towards Creating Shared Value on Sri-Kehati Index - Wibowo, Aulya Yulianti; Rahardja, Liana (Universitas Muhammadiyah Semarang, 2025)
This research explores the influence of environmental performance on the concept of Creating Shared Value (CSV). CSV is a business approach that simultaneously promotes value creation for companies and society. About environmental performance, this study analyzes how environmentally friendly business practices can become a fundamental pillar of CSV strategy. We examine the relationship between corporate actions in reducing negative environmental impacts and increasing shared values through social welfare and business sustainability. By engaging case studies from various industries, we illustrate how proactive measures on environmental issues can generate long-term mutually beneficial benefits focused on creating shared value. UU No. 40 Tahun 2007 reads,